2001
DOI: 10.1111/1467-9507.00156
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Infant‐Mother Attachment: Is the Strange Situation Enough?

Abstract: The purpose of this study was to examine the validity of a new procedure for assessing infant-mother attachment. Sixty children (34 in child care) and their mothers were seen in the Strange Situation (SS) at 17 months and in a new attachment assessment, the California Attachment Procedure (CAP), which does not involve mother-child separations, at 18 months. Overall, children were more likely to be classified as secure in the CAP (83% vs. 67%), but this was particularly true for children with experience in rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Three studies were found that compared an attachment assessment procedure with the reference standard (SSP) [93][94][95] (see Table 1 for a summary of the characteristics of these studies). Two of the studies were conducted in the USA 93,94 and the third study was conducted in Romania.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were found that compared an attachment assessment procedure with the reference standard (SSP) [93][94][95] (see Table 1 for a summary of the characteristics of these studies). Two of the studies were conducted in the USA 93,94 and the third study was conducted in Romania.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies were conducted in the USA 93,94 and the third study was conducted in Romania. 95 The ages of the samples ranged from 17 to 25 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Differential Social Reaction Procedure, first strangers attempted to engage infants in interactive play, followed by the mother interacting with the child in the same way. Limited reliability and validity have been reported for both of these laboratory procedures (Clarke-Stewart et al, 2001;Klein et al, 1982).…”
Section: Assessment Of Attachmentmentioning
confidence: 99%